Chapinero análogo - centro cívico - opus 03 (2018)
My graduation project is about a civic center located in Chapinero, the objective is to integrate the different sectors that make the city of Bogota which are: mobility, culture, business, housing and politics. Therefore, the design process was divided into two areas, an exercise of architectural analogies and the reconstruction of history and morphology from the neighborhood. Talking about analogies, the projects that were used as examples at the same time were divided into four major categories: Buildings Complex, Theme, Form and Grammar. For the categories of buildings complex the chosen projects were, Saynatsalo by Alvar Aalto, Athenian Acropolis and Agora; in Form, Jacobs House by Wright, Tugendhat House by Mies and the Public Library of Stockholm by Asplund; in Theme, Unité d´Habitation of Marseille by Le Corbusier, Scottish Parliament by Miralles and the Town Hall of Gothenburg by Asplund; last but not least in Grammar, Ogliastri Building by Fernando Martínez and once again The Scottish Parliament by Miralles. In the same time, taking into account that civic means what is shared, the principal idea of the project is to eliminate the boundary between each and every one of the city sectors by the creation of a path that I called ?An airway road? which is developed in different levels but always with the premise of integrate mobility, culture, business, housing and politics. For this reason, the project has three metro stations, the town hall of Chapinero, a public library and two housing buildings which are from the state. However, by the creation of different place with various sizes and proportions, the city sectors are also blended into a unity.